Surgical Outcomes of a Second Ahmed Glaucoma Valve Implantation in Asian Eyes with Refractory Glaucoma - Sze Chuan Ong; Maria Cecilia Aquino; Paul Chew; Victor Koh (Journal of Ophthalmology)
Introduction. When the initial glaucoma tube shunt fails in eyes with refractory glaucoma, one option is implantation of an additional Ahmed glaucoma valve (AGV) to control intraocular pressure (IOP). We aim to evaluate the outcomes of a second AGV in Asian glaucoma. Material and Methods. This is a retrospective interventional study, consisting of 21 eyes belonging to 20 patients which underwent a second FP7 AGV. Data collected included demographic characteristics, best corrected visual acuity, IOP, and number of medications. Both intraoperative and postoperative complications or interventions were recorded. The primary outcome measurement was success rate: complete success (IOP ≥5 mmHg and ≤21 mmHg without IOP-lowering medications) and qualified success (IOP ≥5 mmHg and ≤21 mmHg with IOP-lowering medications). Failure was defined as IOP ≥5 mmHg and ≤21 mmHg, reoperations for IOP-related indications, removal of second AGV implant, or loss of light perception. Postoperative complications were included as secondary outcomes. Results. The cumulative failure rates were 9.5%, 20.0%, 32.5%, and 46.0% at six months, one year, two years, and three years of follow-up. At final follow-up, complete success and qualified success rates were 23.8% and 33.3%, respectively; mean IOP and number of medications decreased by 5.6 mmHg (23.9%) and 1.7 mmHg (54.8%), respectively, from preoperative baseline (P<0.01). More common postoperative complications included hypertensive phase (38.1%), corneal decompensation (23.8%), and tube exposure (14.3%). Conclusion. An additional AGV implant had good short and modest long-term effectiveness in reducing IOP following a failed glaucoma tube shunt in Asian eyes, with the mentioned common postoperative complications to be actively monitored and managed.